The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3847/1538-4357/acc65e
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Molecular Structures across the Whole Star-forming Disk of M83: High-fidelity Imaging at 40 pc Resolution

Abstract: We present Atacama Large Millimeter/submillimeter Array (ALMA) imaging of molecular gas across the full star-forming disk of the barred spiral galaxy M83 in CO(J = 1–0). We jointly deconvolve the data from ALMA’s 12 m, 7 m, and Total Power arrays using the MIRIAD package. The data have a mass sensitivity and resolution of 104 M ⊙ (3σ) and 40 pc—sufficient to detect and resolve a typical molecular cloud in the Milky Way with a mass and diameter of 4 × 105 M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 164 publications
4
14
1
Order By: Relevance
“…As a definition, we favor the full duration that the gas is molecular in molecular clouds, and hence is in a prerequisite condition for potential SF. Most cloud studies stem from interests in SF, and it is more relevant to adopt the full duration that the gas can potentially form stars as cloud lifetimes (Scoville & Hersh 1979;Koda et al 2023).…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…As a definition, we favor the full duration that the gas is molecular in molecular clouds, and hence is in a prerequisite condition for potential SF. Most cloud studies stem from interests in SF, and it is more relevant to adopt the full duration that the gas can potentially form stars as cloud lifetimes (Scoville & Hersh 1979;Koda et al 2023).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Second, molecular clouds with and without SF are unevenly distributed in galactic disks. The clouds with SF are mostly along spiral arms, and those without SF are in the interarm regions (e.g., Koda et al 2023). Given disk rotation timescales of order 200 Myr, the clouds cannot move from the interarm regions to spiral arms within the suggested short lifetimes of 5-30 Myr.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have consistently shown that at ∼40-100 pc resolutions, the molecular gas in the spiral arms tends to be brighter and have higher surface densities, velocity dispersions, and pressures than the gas in interarm regions, especially when a strong bar is present (Colombo et al 2014;Sun et al 2018Sun et al , 2020Rosolowsky et al 2021;Koda et al 2023). They have also shown that the slope of the distribution of cloud masses is shallower and truncates at higher masses in the spiral arms than in the interarm regions (Rosolowsky et al 2008;Koda et al 2009;Colombo et al 2014), but that despite the greater amount of star formation in the arms, the depletion time there is not significantly shorter (Querejeta et al 2021).…”
Section: Introductionmentioning
confidence: 91%
“…Much work has been done on understanding how spiral density waves and stellar feedback impact cloud formation, collapse, and dispersal, both from simulations and from observations. There have been several surveys to study the molecular gas in nearby spiral galaxies at the scale of giant molecular clouds (GMCs), such as PAWS (the PdBI Arcsecond Whirlpool Survey), which mapped M51 in CO(1−0) at 40 pc resolution (Schinnerer et al 2013); CANON (CARMA and Nobeyama Nearby Galaxies), which mapped the inner disks of nearby spiral galaxies in CO(1−0) and enabled a focused study of molecular cloud properties using a subsample at 62-78 pc resolution (Donovan Meyer et al 2013); PHANGS-ALMA (Physics at High Angular Resolution in Nearby Galaxies-Atacama Large Millimeter/submillimeter Array), which mapped 90 galaxies in CO(2−1) at ∼100 pc resolution (Leroy et al 2021); and most recently the mapping of the barred spiral galaxy M83 in CO(1−0) at 40 pc resolution (Koda et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the high resolution and sensitivity of the Atacama Large Millimeter/submillimeter Array (ALMA), CO (isotopologue) observations are now routinely possible at cloud scales in nearby galaxies (e.g., Leroy et al 2021;Davis et al 2022;Koda et al 2023;Williams et al 2023). In particular, recent studies modeling multi-CO isotopologues in nearby galaxy centers have revealed that CO opacity is the dominant driver of α CO variations (Israel 2020;Teng et al 2022Teng et al , 2023.…”
Section: Introductionmentioning
confidence: 99%